Penthorum chinense Pursh Compound Ameliorates AFB1-Induced Oxidative Stress and Apoptosis via Modulation of Mitochondrial Pathways in Broiler Chicken Kidneys - Tao, Weilai; Li, Zhenzhen; Nabi, Fazul; Hu, Yu; Hu, Zeyu; Liu, Juan (Frontiers in Veterinary Science, 2021)
Aflatoxin B1 (AFB1) is a carcinogenic mycotoxin widely present in foods and animal feeds; it represents a great risk to human and animal health. The aim of this study was to investigate the protective effects of Penthorum chinense Pursh compound (PCPC) against AFB1-induced damage, oxidative stress, and apoptosis via mitochondrial pathways in kidney tissues of broilers. One-day-old chickens (n=180) were randomly allocated to six groups: control, AFB1 (2.8mg AFB1/kg feed), positive drug (10mLYCHT/kg feed), and PCPC high, medium, and low-dose groups (15, 10, and 5mL PCPC/kg feed, respectively). AFB1 treatment reduced weight gain and induced oxidative stress and kidney damage in broiler tissues; however, PCPC supplementation effectively enhanced broiler performance, ameliorated AFB1-induced oxidative stress, and inhibited apoptosis in the kidneys of broilers. The mRNA expression levels of mitochondria-related apoptosis genes (Bax, Bak, cytochrome c, caspase-9, and caspase-3) were significantly increased, whereas BCL2expressionleveldecreased in the AFB1 group. Supplementation of PCPC to the AFB1group significantly reversed the changes in mRNA expression levels of these apoptosis-associated genes compared to those in the AFB1group. The mRNA levels of NRF2 and HMOX1 in the kidneys of the AFB1 group were significantly reduced compared to those in the control group, whereas PCPC significantly increased the NRF2 and HMOX1 mRNA levels. AFB1 decreased the levels of Beclin1, LC3-I, and LC3-II and increased P53 levels in the kidney compared to those in the control, where as PCPC significantly reversed these changes to normal levels of autophagy-related genes compared to those in the AFB1 group. In conclusion, our findings demonstrated that PCPC ameliorated AFB1-induced oxidative stress by regulating the expression of apoptosis-related genes and mitochondrial pathways. Our results suggest that PCPC represents a natural and safe agent for preventingAFB1-induced injury and damage in broiler tissues.